Catholic Peacebuilding and Mining Integral Peace, Development, and Ecology - Montevecchio, Caesar A.; Powers, Gerard F. (Routledge Studies in Religion, 2022)
This book explores the role of Catholic peacebuilding in addressing the global mining industry. Mining is intimately linked to issues of conflict, human rights, sustainable development, governance, and environmental justice. As an institution of significant scope and scale with a large network of actors at all levels and substantial theoretical and ethical resources, the Catholic Church is well positioned to acknowledge the essential role of mining, while challenging unethical and harmful practices, and promoting integral peace, development, and ecology. Drawing together theology, ethics, and praxis, the volume reflects the diversity of Catholic action on mining and the importance of an integrated approach. It includes contributions by an international and interdisciplinary range of scholars and practitioners. They examine Catholic action on mining in El Salvador, Peru, Colombia, the Democratic Republic of the Congo, and the Philippines. They also address general issues of corporate social responsibility, human rights, development, ecology, and peacebuilding. The book will be of interest to scholars of theology, social ethics, and Catholic studies as well as those specializing in development, ecology, human rights, and peace studies.